In-vitro sperm mucus penetration test for fertility assessment in cows - BENNUR, P C; HONNAPPAGOL, S S; TANDLE, M K (The Indian Journal of Animal Reproduction, 2005)
The estrual cervico-vaginal mucus (CVM) samples were collected from 44 regularly cycling pleuriparous cows prior to artificial insemination and the same were subjected for in-vitro sperm mucus penetration tests like slide, polyethylene and capillary tube tests. Following the collection of CVM the animals were inseminated and screened for pregnancy after 60 days. Among the invitro sperm cervical mucus penetration tests, the slide and capillary tube tests were found to be of diagnostic value in assessing the fertility of cows.